The primacy of vision in Virgil's Aeneid - Smith, R. Alden (University of Texas Press, 2005)
"The essays in this book, derived from papers presented at the First International Symposium on Philodemus, Vergil, and the Augustans, held in 2000, offer a new baseline for understanding the effect of Philodemus and Epicureanism on both the thought and the poetic practices of Vergil, Horace, and other Augustan writers."--Jacket